Effect of W/C Ratio on Durability and Porosity in Cement Mortar with Constant Cement Amount - Kwon, Seung-Jun; Bang, Jin-Wook; Lee, Kwang-Myung; Kim, Yun Yong (Advances in materials science and engineering, 2014)
Water is often added to concrete placing for easy workability and finishability in construction site. The additional mixing water can help easy mixing and workability but causes increased porosity, which yields degradation of durability and structural performances. In this paper, cement mortar samples with 0.45 of W/C (water to cement) ratio are prepared for control case and durability performances are evaluated with additional water from 0.45 to 0.60 of W/C. Several durability tests including strength, chloride diffusion, air permeability, saturation, and moisture diffusion are performed, and they are analyzed with changed porosity. The changing ratios and patterns of durability performance are evaluated considering pore size distribution, total porosity, and additional water content.